Irreducible representations of some two-generator two-groups of nilpotency class two - 615523 Nor Haniza Sarmin; Azhana Ahmad; Simposium Kebangsaan Sains Matematik (ke-12 : 2004 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2004)
40